Taxonomic value of leaf venation and trichome characteristics in some Byttneria L. and Pterocymbium R. Br. (Malvaceae S.L) - Nurshahidah, M.R.; Nabilah, M.; Noraini, T.; Richard, C.C.K.; Ismail, B.S.; Mohd-Arrabe, A.B. (Penerbit Universiti Kebangsaan Malaysia, 2013)
A study on some leaf anatomical characteristics was undertaken on two genera in Malvaceae s.l namely Byttneria L. and Pterocymbium R. Br. The objective was to determine the taxonomic value of leaf venation characteristics especially in identification and classification of species. In the study, five species were chosen, three Byttneria species, namely B. curtisii,B. jackiana, B. maingayi, and two Pterocymbium species, namely P. tinctorium and P. tubulatum. Byttneria and Pterocymbium have been split into two subfamilies, Byttneroideae and Sterculoideae, of Malvaceae s.l respectively. Leaf clearing, staining, mounting and observation under a light microscope were techniques used for the study. Results showed that the similarities and differences in leaf venation could be useful in classification and identification of species. The common characteristics found in all species studied were the presence of entire marginal venation and closed system venation with minimum free ending veinlets in the areolar venation. The variations in the leaf venation can be used to distinguish species, which are complete ultimate marginal venation in B. curtisii and B. maingayi; curved to looped pattern and incomplete, ultimate marginal venation in B. jackiana, P. tubulatum and P. tinctorium. The presence of simple unicellular trichomes in B. jackiana and two types of trichomes (simple unicellular trichomes and multicellular glandular trichomes) and crystals alongside veinlets in P. tubulatum can also be used to further identify these two species from other species studied. Therefore, the study showed that leaf anatomical characteristics in Byttneria and Pterocymbium can be used in species identification and have taxonomic value.